The HSP110/HSP70 disaggregation system generates spreading‐competent toxic α‐synuclein species - Jessica Tittelmeier; Carl Alexander Sandhof; H. Ries; Silke Druffel‐Augustin; Axel Mogk; Bernd Bukau; Carmen Nussbaum‐Krammer (2020)
Article25 May 2020Open Access Source DataTransparent process The HSP110/HSP70 disaggregation system generates spreading-competent toxic α-synuclein species Jessica Tittelmeier Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Carl Alexander Sandhof Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Heidrun Maja Ries Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Silke Druffel-Augustin Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Axel Mogk Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Bernd Bukau Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Carmen Nussbaum-Krammer Corresponding Author [email protected] orcid.org/0000-0002-8689-1363 Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Jessica Tittelmeier Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Carl Alexander Sandhof Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Heidrun Maja Ries Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Silke Druffel-Augustin Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Axel Mogk Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Bernd Bukau Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Carmen Nussbaum-Krammer Corresponding Author [email protected] orcid.org/0000-0002-8689-1363 Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany Search for more papers by this author Author Information Jessica Tittelmeier1, Carl Alexander Sandhof1, Heidrun Maja Ries1, Silke Druffel-Augustin1, Axel Mogk1, Bernd Bukau1 and Carmen Nussbaum-Krammer *,1 1Center for Molecular Biology of Heidelberg University (ZMBH) and German Cancer Research Center (DKFZ), DKFZ-ZMBH Alliance, Heidelberg, Germany *Corresponding author. Tel: +49 6221 54 6825; E-mail: [email protected] EMBO J (2020)39:e103954https://doi.org/10.15252/embj.2019103954 PDFDownload PDF of article text and main figures. Peer ReviewDownload a summary of the editorial decision process including editorial decision letters, reviewer comments and author responses to feedback. ToolsAdd to favoritesDownload CitationsTrack CitationsPermissions ShareFacebookTwitterLinked InMendeleyWechatReddit Figures & Info Abstract The accumulation and prion-like propagation of α-synuclein and other amyloidogenic proteins are associated with devastating neurodegenerative diseases. Metazoan heat shock protein HSP70 and its co-chaperones DNAJB1 and HSP110 constitute a disaggregation machinery that is able to disassemble α-synuclein fibrils in vitro, but its physiological effects on α-synuclein toxicity are unknown. Here, we depleted Caenorhabditis elegans HSP-110 and monitored the consequences on α-synuclein-related pathological phenotypes such as misfolding, intercellular spreading, and toxicity in C. elegans in vivo models. Depletion of HSP-110 impaired HSP70 disaggregation activity, prevented resolubilization of amorphous aggregates, and compromised the overall cellular folding capacity. At the same time, HSP-110 depletion reduced α-synuclein foci formation, cell-to-cell transmission, and toxicity. These data demonstrate that the HSP70 disaggregation activity constitutes a double-edged sword, as it is essential for maintaining cellular proteostasis but also involved in the generation of toxic amyloid-type protein species. Synopsis The HSP110/HSP70 chaperone system plays key roles in general protein folding and the disassembly of protein aggregates. A Caenorhabditis elegans model for α-synuclein aggregation shows that this disaggregase function contributes to the formation of toxic, spreading-competent amyloid species. Co-chaperone HSP-110 depletion impairs general cellular protein folding capacity and inhibits the HSP70 disaggregation machinery. HSP-110 depletion impairs general cellular protein folding capacity. HSP-110 depletion reduces α-synuclein foci formation, cell-to-cell transmission, and in vivo toxicity. The negative effect of HSP-110 depletion on cellular proteostasis overrides the beneficial effect on α-synuclein toxicity in older animals. Introduction Prion proteins can adopt alternative conformations with the ability to self-propagate. This concept of self-templated replication of misfolded protein species was first described for pathogenic protein aggregates in mammalian prion diseases and revolutionized our understanding of infectious agents (Griffith, 1967; Prusiner, 1982). Since their discovery in humans and animals, prions have been found in diverse other organisms, including yeast and bacteria (Wickner, 1994; Yuan & Hochschild, 2017). Work on yeast prions has been instrumental to elucidate basic mechanisms underlying protein-based inheritance (Serio et al, 2000; Sparrer et al, 2000; Wickner et al, 2013). The prion state replicates via a mechanism described as nucleation-dependent polymerization (Jarrett & Lansbury, 1993; Serio et al, 2000; Sparrer et al, 2000), where the rate-limiting step is the initial formation of a seeding-competent oligomeric nucleus consisting of misfolded conformers. This seed then templates the conversion and catalyzes the incorporation of soluble monomers, leading to growth of oligomers into larger highly ordered beta-sheet-rich fibrillar assemblies termed amyloids. The typical architecture of amyloids where the β-strands of individual molecules stack on top of each other is central for their self-templated growth. This structure allows the addition of monomers at the ends of the fibrils. Since this is an intrinsic property of any amyloid-type aggregate, the prion concept is expandable to other amyloid forming proteins. Accordingly, also amyloidogenic proteins associated with neurodegenerative diseases are propagating like prions, including Aβ and tau in Alzheimer disease (AD), α-synuclein (α-Syn) in Parkinson disease (PD), or proteins containing expanded polyglutamine stretches (polyQ) in Huntington's disease (HD) and other polyglutamine diseases (Aguzzi & Rajendran, 2009; Cushman et al, 2010; Prusiner, 2012). In addition to seeded polymerization, there is increasing evidence that fragmentation is essential for efficient prion amplification (Pezza & Serio, 2007), because it exposes more fibril ends at which new monomers are added (Jarrett & Lansbury, 1993; Collins et al, 2004). The importance of fragmentation is exemplified by in vitro techniques of prion amplification, such as real-time quaking induced conversion (RT-QuIC) (Atarashi et al, 2008) and protein misfolding cyclic amplification (PMCA) (Saborio et al, 2001), where fragmentation is achieved mechanically by rigorous shaking or sonication, respectively. Moreover, only mathematical models that take fibril breakage into account are able to accurately predict amyloid growth kinetics observed in vitro and in vivo (Masel et al, 1999; Knowles et al, 2009). Evidence for an essential role of fragmentation in prion propagation in vivo comes from studies in yeast, where faithful propagation of the prion state is dependent on the activity of molecular chaperones, in particular the AAA+ disaggregase HSP104 (Chernoff et al, 1995; Tuite & Lindquist, 1996). Inactivation of HSP104 by guanidine hydrochloride (GdnHCl) or deletion of the HSP104 gene results in prion loss (Chernoff et al, 1995; Tuite & Lindquist, 1996; Grimminger et al, 2004). Importantly, HSP104 does not function in isolation, but cooperates with the HSP70 system to dissolve protein aggregates (Glover & Lindquist, 1998; Masison & Reidy, 2015; Mogk et al, 2018). Mechanistically, substrates are recognized by the HSP70-DNAJ (HSP40) chaperone pair and then handed over to HSP104, which extrudes single polypeptides from the aggregate by threading them through the central pore of the HSP104 hexamer (Lum et al, 2004). This ATP-dependent disaggregation activity leads to the formation of smaller prion fragments, so-called propagons, which have an increased replication capacity and are also more efficiently transferred to daughter cells (Chernoff et al, 1995; Tuite & Lindquist, 1996; Satpute-Krishnan et al, 2007; Tessarz et al, 2008; Winkler et al, 2012; Mogk et al, 2018). Fragmentation is therefore crucial not only for the amplification of prion conformers at the molecular level, but also at the cellular level. The life cycle of amyloid-based prions seems to involve continuous cycles of seeded assembly and fragmentation and only a particular equilibrium of association and dissociation kinetics allow propagation of the aggregated form. While previous work revealed that metazoan cells exhibit disaggregation activity and also contain all co-factors required for cytosolic propagation and dissemination of an ectopically expressed amyloid-like yeast prion (Cohen et al, 2006; Krammer et al, 2009a,b; Hofmann & Vorberg, 2013; Hofmann et al, 2013), the nature of these co-factor(s) was still unclear, since direct homologs of HSP104 are absent from the metazoan cytosol. The recent discovery of a metazoan disaggregation machinery in which a particular HSP110-type nucleotide exchange factor (NEF) cooperates with the human HSP70-DNAJ system to fragment and depolymerize amyloid aggregates (Gao et al, 2015; Scior et al, 2018) has raised the question of whether this activity could prevent or promote the prion-like propagation of amyloid-type aggregates in metazoans and what physiological implications this would have. Although the HSP70 disaggregation machinery is mechanistically different from HSP104/HSP70-mediated disaggregation, the resulting phenotype could still be similar. Since prion-like amplification and intercellular spreading of disease-linked proteins are implicated in the propagation of the pathology in neurodegenerative diseases such as AD and PD, co-factors involved in this process might be potential therapeutic targets. In this study, we have investigated the role of the HSP70 metazoan disaggregation machinery in aggregation and toxicity of amyloid-type aggregates in Caenorhabditis elegans. Diminishing its activity by tissue-specific knockdown (KD) of HSP-110 impaired the resolubilization of amorphous aggregates such as heat shock (HS)-induced firefly luciferase aggregates on the one hand, while mitigating the formation of toxic spreading-competent α-Syn species on the other hand. These results imply that the toxicity associated with amyloids may result not only from aggregate formation but also from aggregate fragmentation. Moreover, a selective impairment of chaperone-mediated remodeling of amyloid-type substrates might be beneficial as it interrupts the vicious circle of fragmentation and seeded polymerization. Results Tissue-specific KD of HSP-110 prevents disassembly of HS-induced firefly luciferase aggregates Our previous work revealed that a specific human HSP70-DNAJ-HSP110 network exhibits in vitro disaggregation activity toward amyloid α-Syn fibrils and detergent insoluble α-Syn extracted from C. elegans (Gao et al, 2015). However, its effect on aggregation and toxicity of α-Syn in vivo has yet to be addressed. Two scenarios are conceivable. The disaggregation activity could either lead to a resolubilization and refolding of aggregated α-Syn, which would result in reduced toxicity. Alternatively, it could contribute to the multiplication of α-Syn aggregates by continuously generating new seeds by fragmentation, analogous to the function of HSP104 and the HSP70-DNAJ system in yeast prion propagation, which would likely increase toxicity. In an effort to assess the role of the metazoan disaggregation machinery in amyloid aggregate propagation in vivo, we employed C. elegans as model organism. Members of the nematode disaggregation system are highly conserved, but less redundant than in the human system (Kirstein et al, 2017). Yet, the cognate HSP70 of the cytosol and nucleus (HSP-1) is involved in a variety of different essential processes in addition to disaggregation, including protein synthesis, clathrin-mediated endocytosis, or chaperone-mediated autophagy (Stricher et al, 2013). The manipulation of this core component of the HSP70 network would lead to a plethora of side effects. Importantly, cooperation of the HSP70 with particular co-chaperones of the DNAJ-protein family (class B-type) and the HSP110-type family of NEFs determines functional specificity with respect to disaggregation (Gao et al, 2015; Mogk et al, 2018). While there are several DNAJ co-chaperones that are functionally redundant, C. elegans has only one cytosolic HSP110-type NEF (HSP-110), which is a key component of the HSP70 disaggregation machinery (Rampelt et al, 2012; Gao et al, 2015; Kirstein et al, 2017; Mogk et al, 2018). By manipulating HSP-110 levels, the disaggregation activity of the HSP70 chaperone network can be specifically modulated. However, since an hsp-110 knockout is lethal and a systemic knockdown (KD) by RNA interference (RNAi) affects growth, development, and fertility (Kamath et al, 2003), we decided to restrict the KD of HSP-110 to the same tissue that expresses the selected substrate protein (e.g., α-Syn). This allows us both to focus on the specific effect on the co-expressed protein of interest and to reduce unwanted side effects in other tissues. To this end, we generated C. elegans strains expressing an RNAi hairpin (HP) construct targeting the hsp-110 mRNA specifically in muscle cells (HPI and HPII) (Winston et al, 2002). To ensure tissue-specific KD of hsp-110 and to prevent systemic RNAi, all strains harbor a loss-of-function mutation in sid-1, a gene coding for a double-stranded RNA transporter, which is essential for inter-tissue transport of dsRNA and systemic RNAi (Winston et al, 2002). To verify a tissue-specific KD of hsp-110, we introduced both hsp-110 hairpin constructs into a strain with endogenously GFP-tagged HSP-110 (HSP-110::GFP). Expression of both hsp-110 hairpin constructs resulted in the loss of GFP fluorescence exclusively in muscle cells, confirming a tissue-specific KD (Fig 1A). Figure 1. Tissue-specific KD of HSP-110 prevents resolubilization of HS-induced firefly luciferase aggregates A. Single plane confocal fluorescent microscopy images of 5-day-old animals harboring GFP-tagged endogenous HSP-110 (HSP-110::GFP). Muscle cells are outlined. M: muscle, H: hypodermis. In animals that co-express hairpin constructs targeting hsp-110 in muscle cells (HSP-110;HPI and HSP-110;HPII), GFP fluorescence is strongly reduced in muscle cells in comparison with control animals, indicating HSP-110::GFP depletion specifically in muscle cells. Scale bar: 10 μm. B. Experimental set-up: Age-synchronized 4-day-old animals were subjected to heat stress for 3 h at 33°C (+HS) and then returned to 20°C or left at 20°C (−HS), respectively. Arrows indicate imaging time points. The −HS controls were imaged at the same time point as the +HS animals after 24 h at 20°C. Maximum intensity projections of fluorescent microscopy z-stacks of animals expressing the indicated transgenes. HS-induced FLUCSM::GFP foci are cleared after a recovery for 24 h at 20°C in the WT background, but persist in the presence of the hsp-110 hairpin construct. Scale bar: 20 μm. C. Quantification of FLUCSM::GFP foci disaggregation. % disaggregation is calculated as 100—ratio of FLUCSM::GFP foci area relative to total muscle area at the +HS 24 h time point to the +HS 2 h time point. Data are displayed as mean ± SEM (in %) (N = 3). Statistical analysis was done using one-way ANOVA with Dunnett's adjustment for multiple comparisons. **P ≤ 0.01. Data information: All strains harbor the sid-1(pk3321) allele. Source data are available online for this figure. Source Data for Figure 1 [embj2019103954-sup-0004-SDataFig1.zip] Download figure Download PowerPoint We then examined whether HSP-110 KD impairs the cellular disaggregation activity by using a well-characterized firefly luciferase reporter (FLUCSM::EGFP) expressed in muscle cells as a model substrate (Gupta et al, 2011). FLUCSM::EGFP remained soluble under ambient growth conditions, but formed numerous aggregates upon acute heat shock (3 h 33°C) in both wild-type (WT) and hsp-110 hairpin expressing animals (Fig 1B). After a 24-h recovery period, FLUCSM::EGFP foci were almost completely dissolved in the WT background, whereas a large fraction of muscle cells still harbored multiple FLUCSM::EGFP foci upon expression of hsp-110 hairpins (Fig 1B and C). Thus, the HSP-110 KD led to persistence of heat-induced amorphous FLUCSM foci, suggesting that disaggregation activity is impaired (Rampelt et al, 2012). KD of HSP-110 reduces cytosolic α-Syn and Q35 foci formation and toxicity We next tested the effect of impaired disaggregation activity on an amyloidogenic substrate. After introducing the hsp-110 hairpin constructs into animals expressing yellow fluorescent protein (YFP)-tagged α-Syn (α-Syn::YFP) in muscle cells (van Ham et al, 2008), we analyzed α-Syn::YFP aggregation and toxicity at days 3, 4, 5, and 6 of life (corresponding to the fourth larval stage, and days 1, 2, and 3 of adulthood). In line with previous reports (van Ham et al, 2008), α-Syn::YFP accumulated into large distinct foci (Fig 2A and B, Appendix Fig S1A and B), which was associated with a progressive decline of muscle function as assessed by a motility assay (Fig 2C and Appendix Fig S1C). Remarkably, the co-expression of hsp-110 hairpins significantly reduced the number of foci and rescued the toxicity of α-Syn::YFP (Fig 2A–C). This suggests that HSP-110-dependent disaggregation activity is required for α-Syn::YFP foci formation and toxicity. Figure 2. KD of HSP-110 reduces cytosolic α-Syn and Q35 foci formation and toxicity A. Maximum intensity projections of fluorescent microscopy z-stacks of 5-day-old nematodes expressing the indicated transgenes are shown. White dashed lines outline the borders of muscle cells. Scale bar: 10 μm. The co-expression of HPI and HPII reduces the amount of α-Syn::YFP inclusions. B. Quantification of α-Syn::YFP foci in 3- to 6-day-old animals. Product of mean foci fluorescence and foci area relative to muscle area is displayed (relFluoFoci). Data are shown as mean ± SEM (in %) (N = 3). Statistical analysis was done using two-way ANOVA with Dunnett's multiple comparison test. **P ≤ 0.01, ***P ≤ 0.001. C. Motility assay as a measure for transgene toxicity. Displayed is the mean number of body bends per 30 s ± SEM (N = 3). Statistical analysis was done using two-way ANOVA with Dunnett's multiple comparison test. **P ≤ 0.01, ***P ≤ 0.001. D. Maximum intensity projections of fluorescent microscopy z-stacks of 6-day-old animals expressing the indicated transgenes. Scale bar: 100 μm. The co-expression of HPI and HPII reduces the amount of Q35::YFP inclusions. E. Quantification of Q35::YFP foci in WT and hsp-110 hairpin background. Shown is the mean ± SEM (N = 3). Statistical analysis was done using two-way ANOVA with Dunnett's multiple comparison test. *P ≤ 0.05, **P ≤ 0.01. F. Motility assay as a measure for transgene toxicity. Displayed is the mean number of body bends per 30 s ± SEM (N = 3). Statistical analysis was done using one-way ANOVA with Dunnett's multiple comparisons test. *P ≤ 0.05, **P ≤ 0.01. G. Maximum intensity projections of fluorescent microscopy z-stacks of 5-day-old nematodes expressing the indicated transgenes. White dashed lines outline the borders of muscle cells. Scale bar: 10 μm. M: muscle, H: hypodermis. Signal outside of muscle cells reveals spreading of α-Syn. H. Quantification of animals showing α-Syn transmission at indicated ages. Displayed is the mean ± SEM (in %) (N = 4). Statistical analysis was done using two-way ANOVA with Dunnett's multiple comparison test. ***P ≤ 0.001. Data information: All strains harbor the sid-1(pk3321) allele, except for the YFP only and Q24 controls. Source data are available online for this figure. Source Data for Figure 2 [embj2019103954-sup-0005-SDataFig2.zip] Download figure Download PowerPoint We next asked whether this effect was specific to α-Syn or whether the same could be observed with another amyloidogenic protein. To test this, we introduced the hsp-110 hairpins into animals expressing 35 polyglutamine (polyQ) residues fused to YFP (Q35::YFP), another substrate that forms fibrillar aggregates in an age-dependent manner (Morley et al, 2002). KD of HSP-110 also reduced the number of foci and toxicity of Q35 (Fig 2D–F, Appendix Fig S1D–F). In sum, HSP-110 activity appears to enhance α-Syn and Q35 foci formation and toxicity. Protein quality control pathways are typically intertwined and inhibiting one pathway sometimes results in upregulation of other components, which could indirectly prevent α-Syn and Q35 misfolding and toxicity in the hsp-110 KD strains. However, comparable expression levels of typical stress-inducible chaperone genes verified that the KD of HSP-110 did not activate the stress transcription factors HSF-1/HSF1 or DAF-16/FOXO (Fig EV1). Since total protein levels of α-Syn::YFP and Q35::YFP remained largely unchanged (Appendix Fig S2), it could also be ruled out that an enhanced degradation was responsible for the observed reduction of foci formation and toxicity. Together with the observations on luciferase reactivation, these data indicate that the effect of HSP-110 KD was specific to its role in substrate disaggregation and was not mediated by indirect compensatory mechanisms. Click here to expand this figure. Figure EV1. KD of HSP-110 does not result in a compensatory activation of the heat shock response A. Quantification of mRNA levels in 4-day-old animals expressing the indicated transgenes or harboring the indicated mutation relative to the −HS control of major HS-inducible genes (2 HSP70s, C12C8.1 and F44E5.4, and the small HSP hsp-16.2) by real-time (RT)–PCR (mean ± SEM, N = 4). Statistical analysis was done using two-way ANOVA with Bonferroni's multiple comparison test. n.s. = not significant. B. Experimental set-up: Age-synchronized 4-day-old animals were subjected to heat stress for 3 h at 33°C (+HS) and then returned to 20°C or left at 20°C (−HS), respectively. Arrows indicate imaging time points. The −HS controls were imaged at the same time point as the +HS animals after 2 h at 20°C. Fluorescent microscopy images of animals expressing GFP under the HS-inducible hsp-16.2 promoter in the control and HSP-110 KD background. Scale bars: 25 μm. The KD of HSP-110 did not evoke an heat shock response under ambient growth conditions (only autofluorescence of the gut granules (*) is visible in −HS strains), but animals were still able to mount an HSR under acute heat stress (+HS). All strains harbor the sid-1(pk3321) allele. Download figure Download PowerPoint HSP104-dependent remodeling of yeast prion aggregates also promotes efficient segregation of seeds into daughter cells, ensuring inheritance of the prion state (Satpute-Krishnan et al, 2007). To test whether the inhibition of HSP-110-dependent disaggregation equally affects α-Syn dissemination in metazoans, we employed our recently developed α-Syn spreading model to monitor the transmission of α-Syn from donor muscle cells into recipient hypodermal cells (Sandhof et al, 2019). The dissemination of α-Syn is age-dependent and can be detected in less than 10% of the animals on day 4 and in more than 90% on day 5 and later in life (Sandhof et al, 2019). KD of HSP-110 significantly reduced the transmission of α-Syn particles between tissues with protein transfer being detected in only 50% of hsp-110 hairpin animals on days 5 and 6 compared to up to 90% of WT animals (Fig 2G and H). Hence, in the absence of HSP-110, α-Syn is inefficiently transferred to neighboring tissues. Since polyQ proteins are not spreading to neighboring tissues in our model system (Sandhof et al, 2019), we could not assess the effect of HSP-110 levels on Q35 spreading. Nevertheless, these findings revealed that the HSP-110-dependent disaggregation activity seems to remodel α-Syn aggregates to create toxic species that can transfer between cells. Overall, these results support the notion that the KD of HSP-110 impairs the HSP70 disaggregation machinery, which on the one hand prevents the removal of amorphous aggregates and on the other hand abolishes the propagation and intercellular transmission of toxic amyloid-type substrates. WT but not NEF-deficient yeast SSE1 can compensate the loss of Caenorhabditis elegans HSP-110 What is the specific contribution of HSP-110 to the observed disaggregation activity in C. elegans? Previous results revealed that the nucleotide exchange activity is necessary for efficient substrate disaggregation in vitro, while its intrinsic ATPase activity is less important (Rampelt et al, 2012). Nevertheless, HSP110s have a substrate binding and a nucleotide binding domain similar to HSP70; therefore, an ATP-driven chaperone-like activity has been proposed for this chaperone family (Shorter, 2011; Mattoo et al, 2013). Indeed, structurally unrelated NEFs, such as Snl1ΔN (BAG-1 homolog) or FES-1 (HSPBP1 homolog), were not able to efficiently substitute an HSP110-family NEF in disaggregation (Rampelt et al, 2012; Kaimal et al, 2017). To investigate this in C. elegans, we took advantage of the high conservation of the chaperones involved in disaggregation, which allows individual members to cooperate across species boundaries (Rampelt et al, 2012). Since yeast NEFs were shown to be able to replace the human HSP110-type NEF in vitro (Rampelt et al, 2012), we introduced extrachromosomal arrays coding for WT and specific mutants of yeast SSE1 (HSP110-type NEF) or FES1 (armadillo-type NEF) into α-Syn::YFP and hsp-110 hairpin expressing animals by microinjection. We found that WT SSE1 could complement for the KD of the endogenous C. elegans HSP-110 and restore the formation of visible α-Syn foci (Fig 3A) and α-Syn toxicity (Fig 3B). Since the transgenes were expressed from an extrachromosomal array, which results in variable expression levels in a variable number of cells, a full complementation was not expected. We next asked whether the interaction of SSE1 with the HSP70-DNAJ system is necessary to mediate substrate disaggregation, which would suggest an important role for the NEF activity of HSP-110. To test this, we employed SSE1N572Y E575A, a double mutant, which is unable to interact with HSP70 (Polier et al, 2008; Rampelt et al, 2012). This mutant did not compensate the loss of HSP-110 and was not able to restore α-Syn foci formation and toxicity (Fig 3A and B). In contrast, an ATPase-deficient SSE1K69M mutant, which hydrolysis ATP 20 times slower than WT SSE1 (Raviol et al, 2006; Rampelt et al, 2012), was capable to reestablish α-Syn foci formation and toxicity similar to WT SSE1 (Fig EV2A and B), suggesting a minor role for a WT ATPase activity in substrate disaggregation. Figure 3. WT but not NEF-deficient yeast SSE1 can compensate the loss of Caenorhabditis elegans HSP-110 A. Maximum intensity projections of confocal microscopy z-stacks of 5-day-old animals expressing the indicated transgenes. White dashed lines outline the borders of muscle cells. Scale bar: 10 μm. The expression of the yeast SSE1N572Y E575A mutant cannot reverse the reduction of α-Syn::YFP foci in the hsp-110 hairpin expressing animals. B. Quantification of motility as a measure for transgene toxicity. Displayed is the mean ± SEM (N = 3) amount of body bends/30 s of animals expressing the indicated transgenes. Statistical analysis was done using two-way ANOVA with Dunnett's multiple comparison test. n.s. = not significant, **P ≤ 0.01, ***P ≤ 0.001. The presence of the yeast SSE1N572Y E575A mutant was not able to suppress the rescue of α-Syn::YFP toxicity in hsp-110 hairpin expressing animals. C. Maximum intensity projections of fluorescent microscopy z-stacks of 5-day-old nematodes expressing the indicated transgenes. White dashed lines outline the borders of muscle cells. M: muscle, H: hypodermis. Scale bars: 10 μm. Signal outside of muscle cells reveals spreading of α-Syn. D. Quantification of animals showing α-